Evaluation of the Antigenotoxic Effect of Quercetin Against Antiepileptic Drug Genotoxicity by Comet Analysis - Fadime Canbolat; Ahmet Ali Berber; Tuğba Nurcan Yüksel; Nihan Akıncı Kenanoğlu (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi, 2023)
Valproic acid (VPA) is among the most commonly used antiepileptic drugs in childhood and adult epilepsy. Although VPA is well tolerated, it can cause life-threatening side effects. VPA has toxic and genotoxic effects. Antioxidants can reverse drugs' toxic and genotoxic effects. Therefore, our study aimed to evaluate the antigenotoxic protective effect of quercetin (QUE) against VPA genotoxicity by in vitro comet assay analysis method. Comet assay analysis was performed in five different groups. Group I; negative control (Sterile H2O), Group II; positive control (H2O2), Group III; VPA was applied in four different dose ranges, Group IV; QUE was applied in four different dose ranges, Group V; For the simultaneous combined administration of VPA and QUE, three different doses of VPA + four different doses of QUE were administered. Low-dose administration of QUE was more effective in ameliorating the damage caused by low-dose VPA (62.5 μg/ml) administration. It is seen that the genotoxic damage caused by the application of 125 μg/ml VPA can be eliminated by QUE at all doses. It was determined that different doses of QUE exhibited a significant antigenotoxic effect against damage caused by 125 µg/mL VPA (P<0.05). In our study, the curative effect of QUE on DNA damage was determined by in vitro comet analysis. Our analysis results showed that QUE ameliorates VPA-induced genetic damage.